AXILLARY LYMPH NODE METASTASIS IN SONOLOGICALLY NODE-NEGATIVE BREAST CARCINOMA - ADARSA S BABU; SUNIL S; JOMINE JOSE (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: This study describes the risk factors for axillary metastasis in patients with sonologically node-negative breast carcinoma and also develops a predictive model to evaluate the risk of axillary metastasis in these patients. Methods: Patients admitted to the Department of General Surgery with carcinoma breast qualifying the inclusion and exclusion criteria were included in the study for a period of 1 year. Study was conducted to determine the risk factors of Carcinoma breast by evaluating some clinical and pathological parameters of carcinoma breast patients. Results: Out of 102 patients, 41 had axillary metastasis, factors found significant with p<0.05 were T stage, grade of tumor, estrogen receptor (ER), progesterone receptor (PR) < human epidermal growth factor receptor 2 (HER 2) neu status, histology, and lymphovascular invasion. Mathematical model was developed by binary logistic regression analysis and the probability of axillary metastasis is obtained. Conclusion: The present study demonstrated that T stage, grade of tumor, ER, PR, HER 2 neu status, histology, and lymphovascular invasion are associated with a high risk of axillary metastasis and the newly generated tool shows a sensitivity of 87.8% and specificity of 93.44% for an optimum cut off of >0.2708.